Update on parasitosis in canines, urban area, city of Guayaquil - Ube Peñafiel, Luz Clara; Cordero Velasco, Jonathan Daniel; Morales Galindo, Abner David; González Puetate, Iván (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2023)
Ancylostomiasis is a disease caused by nematode parasites, which cause problems to both humans and animals in some organs and causes anemia in the health of living beings since they are hematophagous parasites. The objective of this research was to determine the prevalence of Ancylostoma caninum in domestic dogs in the Socio Vivienda 1 sector of the Guayaquil canton, Ecuador. The study was carried out in samples of 151 domestic canines and was analyzed by coprological examinations, the techniques used for the identification of eggs were the flotation method and the concentration method. Of the total number of samples analyzed, 96 positive results were obtained, which represents 63,6 % prevalence in both methods. Finally, there was no association with variables such as age, sex and race.